2017
DOI: 10.1097/md.0000000000006760
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors-2 and -9 (TLR2 and TLR9) gene polymorphism in patients with type 2 diabetes and diabetic foot

Abstract: Toll-like receptors (TLRs) are innate immune receptors that mediate the inflammatory response in diabetes mellitus (DM). The aim of this study is to evaluate the association of TLR2 and TLR9 gene polymorphism in patients with type 2 DM (T2DM) and diabetic foot (DF).The study included 90 subjects divided into group I (30 patients with T2DM and DF), group II (30 patients with T2DM and no evidence of DF), and group III (normal control subjects). TLR2 (1350 T/C, rs3804100) and TLR9 (1237 T/C, rs5743836) genotyping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
17
0
2
Order By: Relevance
“…TLR9 gene polymorphism rs352139 is associated with increased risk of Tuberculosis (TB) in Mexican population but it is associated with decreased risk of TB in Indonesian population [418]. A link between TLR9-1237 T/C gene polymorphism and molecular risk for diabetes foot (DF) disease in patients with T2DM is also observed [419].…”
Section: Tlr Polymorphism In Humans and Their Disease Associationmentioning
confidence: 99%
“…TLR9 gene polymorphism rs352139 is associated with increased risk of Tuberculosis (TB) in Mexican population but it is associated with decreased risk of TB in Indonesian population [418]. A link between TLR9-1237 T/C gene polymorphism and molecular risk for diabetes foot (DF) disease in patients with T2DM is also observed [419].…”
Section: Tlr Polymorphism In Humans and Their Disease Associationmentioning
confidence: 99%
“…We also show that the TLR3 protein level is elevated in the wound-edge epidermis of human diabetic foot ulcers, venous ulcers, and pressure ulcers, contributing to the increased neutrophil and macrophage infiltration in these chronic wounds [ 144 ]. A single-nucleotide polymorphism (SNP) study revealed that TLR4 and TLR9 SNPs and their haplotypes may increase the risk of impaired wound healing in type 2 diabetic patients [ 166 , 167 ]. In line with this, in a streptozotocin (STZ)-induced diabetes mouse model, knockout of TLR2 improved wound healing and reduced oxidative stress, MyD88 signaling, NF-κB activation, and cytokine secretion, suggesting that sustained TLR2 expression and activation may be detrimental to diabetic wounds [ 168 ].…”
Section: Impaired Immune Functions Of Keratinocytes In Chronic Nonmentioning
confidence: 99%
“…Literature data from recent years indicate that an important role in diabetic nephropathy etiopathogenesis may be played by signal transduction pathways that are dependent on TLR2, TLR9, and TLR4 receptors. However, it is not clear which receptor is more pathogenic [154,[158][159][160]. Studies of many research teams indicate increased expression of TLR2 and the presence of endogenous ligands HMGB1 [161,162] and HSP70 [107,122,163], detected on the basis of research conducted on diabetic-induced rats.…”
Section: Diabetic Nephropathy (Dn)mentioning
confidence: 99%